Penggunaan Pola -Ni Shimasu oleh Pembelajar Bahasa Jepang Pemula - Pramesti, Putu Dewi Merlyna Yuda; Adnyani, Kadek Eva Krishna; Hermawan, Gede Satya (Vocational College of Diponegoro University, 2025)
This article discusses the use of the -ni shimasu pattern by beginner learners (1st year university students). The research purpose is described the uses of -ni shimasu pattern by beginner learners. The method is descriptive qualitative. The results are examples of students attaching nouns to the -ni shimasu pattern. Attaching adjectives are not used by students. The nouns used are related to food and drinks, transportation, clothing and accessories, and places. Students tend to provide example sentences by replacing nouns in the pattern without looking at the meaning formed from the sentence. In the use of nouns related to clothing and accessories, students use the theme of recycling in the example in Marugoto A2 basic level 1 as a reference. The results show students are already able to make example sentences using the -ni shimasu pattern but ignore the meaning of the sentence.